O uso do tablet educacional: um estudo na Escola de Referência em Ensino Médio Alfredo de Carvalho, em Triunfo- Pernambuco - Almeida , Maria do Socorro (2016)
This work has as main objective to analyze the use of educational tablet at the School of Reference in High School Alfredo de Carvalho, in the city of Triunfo-PE, checking how is going on the deployment of this technology in educational activities in the classroom at the same time that seeks to identify the difficulties of this merger. The study is characterized as action research, and it is a research that studies the behavior of people falls in exploratory research, rather, as a case study. The survey covers all teachers, the head of Information Technology and students of the third class Lab School investigated for having received the tablet / PC in the previous year. To collect the data, the researcher uses participant observation and questionnaire conducted through Google Docs tool. In seeking to grasp the difficulties faced by the group investigated, the merger of tablet technology / PC as a pedagogical tool, the research favors at the same rate, reflection and how to debate the computer features multiple possibilities for learning, bringing more dynamism and pleasure to act of learning. The survey data externalize the tablet / PC has been positively contributing to student learning by giving them support in carrying out tasks in reading and research, organization of work and understanding of school subjects, enabling them continuity of outside studies the classroom. According to statements of the population studied, this tool has been promoting digital inclusion, personal and professional training of students; shows the school professionals, the importance of using the tablet / PC with responsibility and commitment in order to provide meaningful learning students and guides the direction of the school, indicating that the relevance of this equipment such as supporting the development of learning, should be dealt with Pedagogical Political Project thereof; exposes the government the need to increase digital inclusion public policies for children and young people and at the same time, teachers' training policies to integrate the computer to educational processes of public school. Therefore, open spaces for further research about this educational tool in state public schools in Pernambuco and Brazil, it is a vast and attractive theme.